214k views
1 vote
Simplify the expression:

Simplify the expression:-example-1
User Inas
by
5.5k points

1 Answer

2 votes

Answer:

(⅛)a^(15 - 3m)

Explanation:

[8a^(m+3)]³[¼a^(1 - m)]⁶ a^(x+y) = (a^x)(a^y)

= [8(a^m)a³]³[¼a·a^(-m)]⁶ (a^x)^y = a^(xy)

= 8³a^(3m)a⁹ × (¼)⁶a⁶a^(-6m) Associate like terms

= (8³/4⁶)a¹⁵a^(-3m)

= (2×4)³/4⁶a^(15 - 3m)

= 2³× 4³/4⁶a^(15 - 3m)

= 2³×(1/4³) a^(15 - 3m)

= 2³ × (1/(2²)³ a^(15 - 3m)

= 2³/2⁶a^(15 - 3m)

= (½)³a^(15 - 3m)

= (⅛)a^(15 - 3m)

User Steve Parker
by
5.4k points